Reformas jurídicas al Código Orgánico Integral Penal con relación al procedimiento directo establecido en el artículo 640 - Esparza Mayon, Lilian Lorena (2015)
Through this research is discussed in detail with regard to one of the special procedures established in the Code of Integrated Criminal , such as the Direct method consisting in Art. 640 of the body of law cited, which are set eight rules to regulate how to implement this special procedure . But through this work it is shown that these eight rules listed are not clear enough , leaving many questions both justice operators and users of the service of justice in criminal matters, especially in relation to the time set for 10 days conducting the trial hearing and only 7 days to announce and evacuate the test, remember that although you can suspend judgment hearing , but this is already started on the date indicated in 10 days, therefore could not be ordered suspended or announce new test, because the deadline is the day before the hearing and is already initiated. A clear sign that these rules for the direct process are inadequate found in Resolution No. 146 - 2014 issued by the full Judicial Council dated August 15, 2014 , which issued the " instructional management hearing the direct procedure provided in the Code of Integrated Criminal " and with some steps for implementing these procedures are and who are not in the COIP between salvageable of this resolution in its Article 1 paragraph 1.3 states that the court must " provide that the tax charge and motivate their requests deemed pertinent precautionary and protective measures .. " is the prosecutor whether to motivate his indictment in flagrante hearing it, but based on what items can the Fiscal motivate his indictment when a flagrant only has the referential part informative . It is through this resolution complement the gaps that have the COIP to the direct method, however I believe that this resolution is not sufficient because on one hand it was right to bring legal reform and not issue a ruling , and on the other hand only solves one of the questions or issues raised in my thesis , leaving the other questions and exposed.- So I believe that proper regulation of this procedure establishing clearer rules kick while extending the deadline because it is too short to ensure the right to defense. Also this problem is of great significance and importance in the legal work of the country and through this work can improve the legal framework . That is why I selected this research topic over letting my graduate career will serve as a source query, to society and the way it would be fulfilling the main objective is to have a more solid legal framework criminal who has recently been applied